Getting back into the labor market: The effects of start-up subsidies for unemployed females - Marco Caliendo; Steffen Künn (Institute for the Study of Labor (IZA), 2012)
A shortage of skilled labor and low female labor market participation are problems many developed countries have to face. Besides activating inactive women, one possible solution is to support the re-integration of unemployed women. Due to female-specific labor market constraints (preferences for flexible working hours, discrimination), this is a difficult task, and the question arises whether active labor market policies (ALMP) are an appropriate tool to do so. Promoting self-employment among the unemployed might be promising. Starting their own business might give women more independence and flexibility in allocating their time to work and family. Access to long-term informative data allows us to close existing research gaps, and we investigate the impact of two start-up programs on long-run labor market and fertility outcomes of female participants. We find that start-up programs persistently integrate former unemployed women into the labor market and partly improve their income situations. The impact on fertility is less detrimental than for traditional ALMP programs.
Keywords: J68; C14; H43; 330; start-up subsidies; evaluation; long-term effects; female labor force participation; fertility